A WLE/Alliance city food system profile is being used as a tool to influence public discourse, educate university students and strengthen policy in the city of Cali, Colombia - CGIAR Research Program on Water, Land and Ecosystems (2021)
Since its launch and after many presentations to diverse audiences, the Cali food system profile, created by the Alliance of Bioversity and CIAT and funded by WLE, has been used as a communication tool to raise awareness, promote food issues on the public agenda, integrate diverse stakeholders, highlight the city’s challenges and improve decision making.